Фраземи со компонента мачка/мачор во македонскиот и во рускиот jaзик - Мирчевска-Бошева, Биљана (SlavVaria, 2025)
Phrasemes with a component cat in Macedonian and Russian languages. This paper aim is to analyse the phrasemes in the Macedonian and Russian languages that contain the zoonymic component cat. The exceptional importance and presence of the cat in human life has led to numerous associations related to it, as well as numerous phrasemes. The purpose of this paper is to perceive the associations represented in the phrasemes, as well as to perceive the differences and similarities in this segment of the phraseological fund of the two languages.